1981
DOI: 10.1210/endo-109-4-1295
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Reduction in Nocturnal Pineal Melatonin Levels in Female Rats1

Abstract: Pineal N-acetyltransferase (NAT) activity and radioimmunoassayable levels of melatonin were compared in 2-month-old (young), 12-month-old (middle-aged), and 29-month-old (old) female rats killed at 1600 h (during the light) and at 2300 h (4 h after darkness onset) and 0100 h (6 h after darkness onset). During the light period, NAT levels were equivalent in pineals from each age group. With the onset of darkness NAT levels rose sharply and were again equivalent in all groups at 2300 h. At 0100 h pineal NAT valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
105
3
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(122 citation statements)
references
References 10 publications
13
105
3
1
Order By: Relevance
“…), sex and light regimen have to be considered, too. The pineal MEL levels in middle-aged female rats (12-month-old) range between levels of young adult and old rats (Reiter et al 1981), whereas in the male rats of the same age a loss of night MEL plasma peak was found (Rasmussen et al 2001).…”
Section: Discussionmentioning
confidence: 95%
“…), sex and light regimen have to be considered, too. The pineal MEL levels in middle-aged female rats (12-month-old) range between levels of young adult and old rats (Reiter et al 1981), whereas in the male rats of the same age a loss of night MEL plasma peak was found (Rasmussen et al 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Other groups have also confirmed that oestrogen treatments were able to enhance neurogenesis in the dentate gyrus of the hippocampus in adult animals (Brinton 2009;Pawluski et al 2009). Reiter et al (1981) reported a marked decline in nocturnal pineal melatonin levels with ageing in female rats. Okatani et al (2000) observed that although nocturnal serum melatonin levels in premenopausal women declined moderately from 17 to 45 years of age, it showed an increase during the period from 46 to 50 years of age.…”
mentioning
confidence: 99%
“…The amount of melatonin and its main urinary metabolite, 6-sulphatoxymelatonin decreases with the advancing age [14,15]. In humans, melatonin production not only diminishes with age, but it is also significantly lower in many age-related diseases such as cardiovascular disease [16,17].…”
Section: Discussionmentioning
confidence: 99%